Introduction to solid modeling using SolidWorks 2011 - Howard, William E. [ (William Edward)] , 1957-; Musto, Joseph C. (McGraw-Hill Science, 2012)
"Introduction to Solid Modeling Using SolidWorks® 2011 presents "keystroke-level" tutorials, providing users new to the SolidWorks® program with all the detail they need to become confident using the software. Topics are illustrated and infused with examples from the real world such as flanges, brackets, helical springs, and more. Additionally, this easy-to-use guide has modular chapters, allowing for flexible organization of a course or self-study.Accessible and updated for the newest version of software, Introduction to Solid Modeling Using SolidWorks® 2011 by Howard and Musto relates solid modeling exercises to engineering concepts in a way that introduces the engineering design process while simultaneously building student proficiency with a state-of-the-art software tool" Provided by publisher